3D Array of Bi2S3 Nanorods Supported on Ni Foam as a Highly Efficient Integrated Oxygen Electrode for the Lithium‐Oxygen Battery. (5th March 2018) - Shu, Chaozhu; Liu, Yunhan; Long, Jianping; Chen, Xianfei; Su, Yang
Abstract: Bismuth sulfide nanorod array is directly grown on nickel foam (R‐Bi2 S3 /NF) to serve as a completely carbon and binder‐free 3D porous oxygen electrode material for lithium‐oxygen (Li‐O2 ) batteries. The synergistic effect of the fast kinetics of electron transport and gas and electrolyte diffusion provided by the continuous free‐standing network structure and the excellent electrocatalytic activity of the bismuth sulfide nanorod array enables outstanding performance of the oxygen electrode. Li‐O2 battery with the free‐standing R‐Bi2 S3 /NF oxygen electrode exhibits high energy efficiency (78.7%), good rate capability (4464 mA h g −1 at 1500 mA g −1 ), as well as excellent cyclability (146 cycles) while maintaining a moderate specific capacity of 1000 mA h g −1 . The effect of cathodes with different reactant (O2 ) and intermediate (LiO2 ) adsorbability on the product (Li2 O2 ) growth model is studied by first‐principle calculations. The strong O2 adsorption and weak LiO2 adsorption on Bi2 S3 drives the growth of large‐size Li2 O2 particles via solution growth model. Remarkably, the large‐area pouch‐type Li‐O2 battery delivers an energy density of 330 Wh kg −1 . The present results open up a promising avenue toward developing novel electrode architecture for high‐performance Li‐O2 batteries through controlling morphology and functionality of porous electrodes. Abstract : Bismuth sulfide as an integrated carbon‐free cathode is studied to improve the stability of lithium‐oxygen batteries. Through the synergy of experiment and theory, an approach to the product formation mechanism is developed, which is different from the mechanism of the traditional carbon cathode. This integrated cathode based large‐area pouch‐type lithium‐oxygen battery delivers an energy density of 330 Wh kg −1 .